1976
DOI: 10.1287/opre.24.6.1056
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Computational Study on an In-Core, Out-of-Core Primal Network Code

Abstract: This paper presents extensive computational experience with a special-purpose primal simplex code using the augmented threaded index method for solving capacitated and uncapacitated transshipment and transportation problems. This code is distinguished from other codes for solving such problems in that not all of the data resides in central memory simultaneously; thus, it is referred to as an in-core, out-of-core code. The major advantages of such a code over an in-core code are (1) it can solve problems that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This belief is partly based on the work reported in (11] wh ich illustrates that general network codes can be designed which only requi re two more node length array s than the PAP E code . Further , Karney and Klingman [16] indicate that these simplex based codes do not suffer undue increases in solution times by keeping a portion of the problem data on external computer memory network is large ly due to the time spent in changing node potentials (dual variable values) (7 , 111 . Experience has shown that the node potentials change 1½ times, on the average , for the label-correcting algorithms [7] and 6-10 times for the mini mum cost flow network.…”
Section: Computational Resultsmentioning
confidence: 99%
“…This belief is partly based on the work reported in (11] wh ich illustrates that general network codes can be designed which only requi re two more node length array s than the PAP E code . Further , Karney and Klingman [16] indicate that these simplex based codes do not suffer undue increases in solution times by keeping a portion of the problem data on external computer memory network is large ly due to the time spent in changing node potentials (dual variable values) (7 , 111 . Experience has shown that the node potentials change 1½ times, on the average , for the label-correcting algorithms [7] and 6-10 times for the mini mum cost flow network.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Earlier research with pure network problems [19], [20], [33] has established that certain factors play a critical role in determining solution speed. These are: start procedures, pivot selection techniques, degeneracy, tolerance levels, Big-M value, and pivot tie-breaking rules.…”
Section: Computational Evaluation Of Solution Strategiesmentioning
confidence: 99%
“…A transshipment problem with 1100 nodes and 3700 arcs is a very large problem to solve in a reasonable time on such a computer since this is an LP with 1100 constraints and 3700 variables. Using our codes [13,26] we were able to solve this problem in 37 seconds compared with 45 minutes using the GM transshipment code on the same computer. aiding in the planning of loans, purchases, and sales of securities, etc.…”
Section: Applicationsmentioning
confidence: 99%